ENHANCING STUDENT BEHAVIOR THROUGH IMPLEMENTATION OF WEB-BASED CHARACTER BUILDING FOR STUDENTS AT HISTORY EDUCATION STUDY PROGRAM IN UNIVERSITAS NEGERI JAKARTA - Umasih, Desy Safitri, Sri Nuraini, Taufik Rihatno, Arifin Maksum, Arita Marini, Apri Wahyudi (International Journal of Advanced Science and Technology, 2020)
The purpose of this study was to enhance student behavior through implementation of web-based character building for 33 students at history education study program in Universitas Negeri Jakarta in Jakarta in Indonesia. This research included two cycles to implement web-based character building at URL: https://pembangunankarakter.wixsite.com/characterbuilding consisting of character building in teaching learning process, school culture, extracurricular activities, and through community involvement. The results presented that student behavior related to the student achievement behavior, the student motivational behavior, and the student social-emotional behavior in cycle 1 and 2 arrived at 68.59 % and 82.64 %. It can be concluded that implementation of web-based character building can enhance student behavior for 33 students at history education study program in Universitas Negeri Jakarta in Jakarta in Indonesia.